Forty years of allocated seats for Sami medical students : has preferential admission worked? - Gaski, Margrete; Abelsen, Birgit; Hasvold, Toralf (Australian Rural Health Education Network, 2008)
This article examines the effects of a special admission policy for Sami medical students in Norway. In the 1960s, public health and health care were found to be poorer in Sami communities than in the rest of Norway. There were few doctors and none of them spoke Sami. Sami school leavers found it difficult to gain admittance to medical schools. In response to this situation, the medical faculty at the University of Bergen adopted a special admissions policy for Sami students in 1963. The University of Tromsø did the same in 1991. In this study we have analyzed whether the allocated Sami seats produced the desired outcomes. In assessing the outcomes, the study takes into account the considerable improvements in public health and health care in the last 40 years, wider use of the Sami language and generally higher educational achievements among the Sami. This retrospective study was set in two medical schools in Norway. The study population is students admitted to medical school on allocated Sami seats, in the two periods 1963-1986 at the University of Bergen, and 1991-2000 at the University of Tromsø. After a question identified the Sami students, whether they had practised or were practising medicine was determined. In total 38 students were admitted on the allocated Sami seats, and 32 graduated. Of the candidates, 93% had practised medicine in one of the two northernmost counties in Norway. Graduates during the 1960s and 1970s were more likely to have worked as GPs in the main areas of Sami habitation than the Sami physicians who graduated later. The Sami doctors admitted to medical school on allocated Sami seats have practiced in Finnmark or Troms, counties where most of the Sami people live. However, this study was unable to establish whether admission on these grounds led to more Sami doctors working in the main areas of Sami habitation. Regarding the workplace location variable, there were no differences between Sami and other physicians from the northern part of Norway who were educated at the University ...